Environment I Project (EPI) in Madagascar (1991-1995) - World Bank (Washington, DC, 2012)
The objective of the project is to improve the environmental management capacity in Madagascar through the implementation of institutional development and emergency actions. Project components included: (i) protection and management of biodiversity; (ii) community-based soil conservation and watershed management; (iii) mapping and remote sensing for improved natural resources management; (iv) improved land security through cadastral surveys; (v) environmental sensitization, education and training; and (vi) research and institution building and reinforcement, (e.g., for natural forest management). Lessons learned: local participation, integration of environmental concerns into national and local decision-making and multi-donor input at the design stage increased the effectiveness of the project. The second environment project under preparation seeks to incorporate such concerns more strategically at the design stage.